Determination of the Ratio Austenite Phase in 52100 Steel after the Thermal Treatment (Latakia University Journal -Basic Sciences Series, 2021)
The diffracted intensity from a phase depends on variety of factors such as structure factor, Lorentz polarization …etc.In this research the above mentioned factors have been calculated for both   and .In addition, the ratio between diffracted intensities is  has been determined with value  , which corresponds to a depth 0.25mm from the studied steel sheet.The variation of diffracted intensity  as a function of depth of surface sheet reveals a peak at 630 au at depth 0.4 mm which indicated to site of martinsite formation.        Keywords: austenite phase, martinsite phase, diffracted intensity, structure factor, volume fraction.